Analysis of Health Service Factors on Patient Satisfaction at The Dental Clinic - Sabang, Novrizal; Asriwati, Asriwati; Fitriani, Arifah Devi (Universitas Prima Indonesia, 2024)
Puskesmas is a technical implementation unit of the District/City Health Office that is responsible for providing first-level health services in a comprehensive, integrated and sustainable manner. The main problem as a health service institution with many competitors is the service provided whether it is in accordance with the expectations of patients/ consumers or not. The purpose of the study was to determine the factors of health services on patient satisfaction. The research design used quantitative methods conducted by analytical surveys with a cross sectional study approach. The samples in this study were 74 patients, research conducted in Simpang Kanan Health Center, Simpang Kanan District, Aceh Singkil Regency. Where the sampling technique in this study used purposive sampling techniques with inclusion criteria are able to communicate well and have ever come for treatment. Exclusion criteria are new patients seek treatment and not able to communicate well. Based on the results of statistical tests, the p-value of all variables is <0.05 where there is an influence on waiting time, competence, financing system, facilities, and comfort. After a multivariate test, it is known that the facility variable is the most influential factor on patient satisfaction. It is recommended that the Simpang Kanan Health Center be able to improve discipline, competence, and public health service facilities in an effort to increase patient satisfaction.